EXAMINING RETRO MARKETING ADS FROM THE PERSPECTIVE OF NEUROMARKETING: THE EXAMPLE OF NESTLE BRAND - Yücel, Nurcan; Yücel, Atilla; Gür, Yunus Emre; Gündüz, Koray (My University, 2020)
As a result of the changes experienced today, importance of brands in addressing the emotions of the consumers in order to stand out from the competitors and provide a competitive advantage has increased. Retro marketing is used in marketing communication messages in order to create an emotional connection with the brand and to make it a part of daily life. Thus, firms aimed to remind consumers the past, make them to yearn for the past, and to buy the retro branded products. The aim of this study is determined the thoughts in subconscious of their and response levels of the consumers to Retro ads by using the EEG Analysis Method from the neuromarketing techniques. Therefore, the advertising by Retro marketing, which is accepted to have a significant effect on consumers in the literature, combined with the neuromarketing approach and putting forward the effectiveness of the Retro ads with EEG Analysis Method emphasize the importance of the study. This study is among the very first studies connecting Retro marketing and neuromarketing. The outcomes of the experiments performed led to conclude that the retro marketing ad prepared successsfully has a positive effect on consumers.
Keywords: İşletme